2009
DOI: 10.2113/jeeg14.2.63
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Resistivity Imaging Revealed the Spatial Properties of Mine Tailing Ponds in the Sierra Minera of Southeast Spain

Abstract: Mine tailing ponds are environmental hazards because of high susceptibility to leaching and erosion by water and wind. Vegetation establishment is an effective technique to reclaim tailing ponds but requires knowledge of the spatial relationship between the structural composition and physical and chemical properties of soils. In this study we have demonstrated the use of electrical resistivity imaging (ERI), combined with soil chemical analyses, to determine the structural and chemical composition of mine tail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 25 publications
(30 reference statements)
2
45
0
1
Order By: Relevance
“…The consistencies of the results of this work with other recent studies (e.g., Martínez-Pagán et al 2009;Martín-Crespo et al 2010) show geoelectrical methods to be a promising tool for characterizing AMD generation and flow direction in the tailings impoundment. Further geophysical research on AMD problems is needed, however, to define research procedures more sharply and allow reliable monitoring of continuous sulfide oxidation processes, and generation and behavior of AMD.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The consistencies of the results of this work with other recent studies (e.g., Martínez-Pagán et al 2009;Martín-Crespo et al 2010) show geoelectrical methods to be a promising tool for characterizing AMD generation and flow direction in the tailings impoundment. Further geophysical research on AMD problems is needed, however, to define research procedures more sharply and allow reliable monitoring of continuous sulfide oxidation processes, and generation and behavior of AMD.…”
Section: Discussionsupporting
confidence: 81%
“…Painter et al (2000) obtained resistivity values \20 Ohm m for coal tailings and AMD-saturated waste rock in southeastern Ohio, USA, and Shemang et al (2003) attributed values between 1 and 20 Ohm m to interaction of mine wastes with soils near a Cu-Ni mine dump in NE Botswana. Martínez-Pagán et al (2009) found resistivity values of \8 Ohm m associated with fine tailings, having large amounts of Cd, Cu, Pb and Zn and of pH \ 5, at El Table 3).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In order to combine a good penetration depth, a reasonable vertical and horizontal resolution and a good signal‐to‐noise ratio, the Wenner‐Schlumberger array has been chosen for this study. This array has been successfully used by other authors in similar studies (e.g., Martínez‐Pagán et al ).…”
Section: Methodsmentioning
confidence: 98%
“…Wastes generated by the mining industry are often subject to secondary movement that is facilitated by air and water (erosion). The transport of this material causes environmental problems due to concentration of heavy metals such as arsenic (Armienta et al, 2008), lead (Mendez et al, 2008), copper (Martínez-Pagán et al, 2009) and mercury (Melamed and Villas-Bôas, 1998) in the tailings. Environmental risk that is apparent for tailings is a powerful driver for cost-effective remedial solutions.…”
Section: Introductionmentioning
confidence: 99%